Overcoming Anode Instability in Solid‐State Batteries through Control of the Lithium Metal Microstructure. (9th November 2022) - Singh, Dheeraj Kumar; Fuchs, Till; Krempaszky, Christian; Mogwitz, Boris; Burkhardt, Simon; Richter, Felix H.; Janek, Jürgen
Abstract: Enabling the lithium metal anode (LMA) in solid‐state batteries (SSBs) is the key to developing high energy density battery technologies. However, maintaining a stable electrode–electrolyte interface presents a critical challenge to high cycling rate and prolonged cycle life. One such issue is the interfacial pore formation in LMA during stripping. To overcome this, either higher stack pressure or binary lithium alloy anodes are used. Herein, it is shown that fine‐grained ( d  = 20 µm) polycrystalline LMA can avoid pore formation by exploiting the microstructural dependence of the creep rates. In a symmetric cell set‐up, i.e., LiǀLi6.25 Al0.25 La3 Zr2 O12 (LLZO)ǀLi, fine‐grained LMA achieves > 11.0 mAh cm −2 compared to ≈ 3.6 mAh cm −2 for coarse‐grained LMA ( d  = 295 µm) at 0.1 mA cm −2 and at moderate stress of 2.0 MPa. Smaller diffusion lengths (≈ 20 µm) and higher diffusivity pathway along dislocations ( D d  ≈ 10 −7  cm 2  s −1 ), generated during cell fabrication, result in enhanced viscoplastic deformation in fine‐grained polycrystalline LMA. The electrochemical performances corroborate well with estimated creep rates. Thus, microstructural control of LMA can significantly reduce the required stack pressure during stripping. These results are particularly relevant for "anode‐free" SSBs wherein both the microstructure and the mechanical state of the lithium are critical parameters. Abstract : Microstructural dependence of creep rates in lithium metal anode (LMA) is exploited to significantly reduce the required stack pressure during stripping. A stable Liǀsolid–electrolyte interface for over 110 h is achieved at a moderate pressure of 2.0 MPa under an anodic load of 0.1 mA cm −2 .